Development and Feasibility Assessment of a Rotational Orthosis for Walking with Arm Swing - Fang, Juan; Xie, Qing; Yang, Guo-Yuan; Xie, Le (Frontiers in Neuroscience, 2017)
Interlimb neural coupling might underlie human bipedal locomotion, which is reflected in the fact that people swing their arms synchronously with leg movement in normal gait. Therefore arm swing should be included in gait training to provide coordinated interlimb performance. The present study aimed to develop a Rotational Orthosis for Walking with Arm Swing (ROWAS), and evaluate its feasibility from the perspectives of implementation, acceptability and responsiveness. We developed the mechanical structures of the ROWAS system in SolidWorks, and implemented the concept in a prototype. Normal gait data were used as the reference performance of the shoulder, hip, knee and ankle joints of the prototype. The ROWAS prototype was tested for function assessment and further evaluated using five able-bodied subjects for user feedback. The ROWAS prototype produced coordinated performance in the upper and lower limbs, with joint profiles similar to those occurring in normal gait. The subjects reported a stronger feeling of walking with arm swing than without. The ROWAS system was deemed feasible according to the formal assessment criteria.